2008
DOI: 10.1261/rna.940708
|View full text |Cite
|
Sign up to set email alerts
|

Sm protein methylation is dispensable for snRNP assembly in Drosophila melanogaster

Abstract: Sm proteins form stable ribonucleoprotein (RNP) complexes with small nuclear (sn)RNAs and are core components of the eukaryotic spliceosome. In vivo, the assembly of Sm proteins onto snRNAs requires the survival motor neurons (SMN) complex. Several reports have shown that SMN protein binds with high affinity to symmetric dimethylarginine (sDMA) residues present on the C-terminal tails of SmB, SmD1, and SmD3. This post-translational modification is thought to play a crucial role in snRNP assembly. In human cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 40 publications
(56 reference statements)
1
39
0
Order By: Relevance
“…PRMT7 belongs to the type II methyltransferase capable of generating symmetric dimethyl-arginine (SDMA) modifications of proteins (19). It has been indicated that PRMT7 may participate in a variety of physiologic processes, e.g., PRMT7 plays a role in male imprinted gene methylation by catalyzing H4R3me2s (20), and the SnRNP assembly and biogenesis are thought to be mediated by PRMT7 via posttranslational modification (21). Also, PRMT7 is involved in regulation of the DNA damage repair genes by mediating H2AR3me2s and H4R3me2s (22).…”
Section: Introductionmentioning
confidence: 99%
“…PRMT7 belongs to the type II methyltransferase capable of generating symmetric dimethyl-arginine (SDMA) modifications of proteins (19). It has been indicated that PRMT7 may participate in a variety of physiologic processes, e.g., PRMT7 plays a role in male imprinted gene methylation by catalyzing H4R3me2s (20), and the SnRNP assembly and biogenesis are thought to be mediated by PRMT7 via posttranslational modification (21). Also, PRMT7 is involved in regulation of the DNA damage repair genes by mediating H2AR3me2s and H4R3me2s (22).…”
Section: Introductionmentioning
confidence: 99%
“…Although protozoa, yeast and even models such as Drosophila, can be advantageous in studying biological processes such as snRNP assembly [44,59,60], results obtained with such model organisms should be interpreted with caution in regards to SMA pathogenesis. In these models, snRNP assembly may function by different mechanisms owing to ortholog divergence of proteins, which can be quite significant in certain models [44].…”
Section: Small Nuclear Ribonucleoprotein Assemblymentioning
confidence: 99%
“…The requirement for methylation in snRNP assembly has been recently tested in Drosophila. The use of two distinct lines that synthesise modified isoforms of SmD1, in which either the entire RG-rich tail is deleted or the arginine residues are substituted by lysine, shows that in Drosophila the RG-rich tail of SmD1 is required for cell viability, whereas the symmetric dimethylation of C-terminal arginine residues in SmD1 is required neither for viability nor for snRNP assembly (Gonsalvez et al, 2008). These data suggest that the sDMA modification of SmD1 is dispensable for snRNP particle assembly.…”
Section: Introductionmentioning
confidence: 99%
“…In csul animals, the major Sm-class snRNPs are expressed normally (Gonsalvez et al, 2006), suggesting that csul is dispensable for snRNP assembly in Drosophila. In addition, flies express an orthologue of PRMT7, Dart7 (Art7, CG9882) (Boulanger et al, 2004), which is also required for sDMA modification of Sm proteins in vivo (Gonsalvez et al, 2008). Unlike csul, Dart7 is an essential gene (Gonsalvez et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation